Hemostatic powder TC‐325 treatment of malignancy‐related upper gastrointestinal bleeds: International registry outcomes. Issue 11 (28th June 2021) - Hussein, Mohamed; Alzoubaidi, Durayd; O'Donnell, Michael; de la Serna, Alvaro; Bassett, Paul; Varbobitis, Ioannis; Hengehold, Tricia; Ortiz Fernandez‐Sordo, Jacobo; Rey, Johannes W; Hayee, Bu'Hussain; Despott, Edward J; Murino, Alberto; et al.
Abstract: Background and Aim: Upper gastrointestinal tumors account for 5% of upper gastrointestinal bleeds. These patients are challenging to treat due to the diffuse nature of the neoplastic bleeding lesions, high rebleeding rates, and significant transfusion requirements. TC‐325 (Cook Medical, North Carolina, USA) is a hemostatic powder for gastrointestinal bleeding. The aim of this study was to examine the outcomes of upper gastrointestinal bleeds secondary to tumors treated with Hemospray therapy. Methods: Data were prospectively collected on the use of Hemospray from 17 centers. Hemospray was used during emergency endoscopy for upper gastrointestinal bleeds secondary to tumors at the discretion of the endoscopist as a monotherapy, dual therapy with standard hemostatic techniques, or rescue therapy. Results: One hundred and five patients with upper gastrointestinal bleeds secondary to tumors were recruited. The median Blatchford score at baseline was 10 (interquartile range [IQR], 7–12). The median Rockall score was 8 (IQR, 7–9). Immediate hemostasis was achieved in 102/105 (97%) patients, 15% of patients had a 30‐day rebleed, 20% of patients died within 30 days (all‐cause mortality). There was a significant improvement in transfusion requirements following treatment ( P  < 0.001) when comparing the number of units transfused 3 weeks before and after treatment. The mean reduction was one unit per patient. Conclusions: Hemospray achieved high rates of immediate hemostasis, with comparable rebleed rates following treatment of tumor‐related upper gastrointestinal bleeds. Hemospray helped in improving transfusion requirements in these patients. This allows for patient stabilization and bridges towards definitive surgery or radiotherapy to treat the underlying tumor.